PEMBATASAN PERMOHONAN KASASI DALAM PENERAPANNYA (UNDANG-UNDANG MAHKAMAH AGUNG NOMOR 5 TAHUN 2004 PASAL 45A AYAT 2) - Emmy Sri Mauli Tambunan (Universitas Batanghari Jambi, 2014)
Legislation has been trying to set up restrictions on the matter either formal or substantial, yet virtually all banged on human rights justice seekers. Cassation is the remedy granted to the accused and the public prosecutor when a court verdict against the object to drop him. In its application of LAW MA No.5 2004 Article 45A Clause 2 it turns out having problems because there are still many cases of Cassation who ended up in MA.The reason of Cassation Petition submitted refers to the CRIMINAL PROCEDURE CODE and the jurisprudence. So it is important not to appeal Restrictions or not useful. That is an important issue is the improvement of the quality and morale of the judges so that the judge can be a fair verdict spawned the present bottom. Thus the petition effort of Cassation will be limited.Keyword : Cassation, human rights, the quality and morale of the judges